IOT - development of a home automation system 7 - Chua, Eric Jee Hon (Nanyang Technological University, 2023)
Internet of Things (IoT) technology is quickly evolving, revolutionizing numerous aspects of our daily lives like home automation. This project illustrates the design, development and deployment of a user-friendly and efficient IoT-enabled home automation system. Android Studio, Firebase, the ESP32 microcontroller, LEDs and a magnetic contact switch are among the hardware and software elements used by the system. The main goal of this project is to design and develop a comprehensive IoT-enabled home automation system that addresses frequent homeowners’ issues. A mobile application is created using Android Studio that integrates with Firebase to have access to real-time data regarding the states of the smart gadgets. The bi-directional communication between the mobile application and the physical smart gadgets is made possible by the integration of the ESP32 microcontroller. With the mobile application, homeowners can effortlessly check the status of the door and LEDs. Furthermore, homeowners can control the LEDs remotely. Homeowners can view the smart gadgets’ activity history which allows them to identify any unauthorized and suspicious activities. In conclusion, this project delivers an IoT enabled home automation system that satisfies the evolving needs of homeowners. The system provides seamless control and monitoring over smart gadgets for the convenience of homeowners. This project is a useful and creative addition the field of home automation as technology continues to change how homeowners interact with their surroundings.